Knowledge and practices among primary school children regarding use of sanitary latrine in Kushtia municipality of Bangladesh - Reza, Hasan Mahfuz; Saha, Ashees Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: The purposes of sanitation are to provide a healthy living environment for everyone, to protect the natural resources such as surface water, ground water, soil and to provide safety; security and dignity for people when they urinate or defecate. Effective sanitation system provide barrier between excreta and humans in such a way as to break the disease transmission cycle. The study was conducted to explore the level of knowledge and practices of primary school children regarding use of sanitary latrine. Methods: A cross sectional survey was carried out among 372 children in 4 selected primary schools. Data were collected using questionnaires regarding socio-demographic characteristics of children, their knowledge and practices of using sanitary latrine. Results: Study results showed majority of the students (84.9%) heard the name of sanitary latrine and 15.1% students didn’t. The study showed that about 80.1% students had pucca/water seal latrine and 18.8% students had kantcha latrine in their houses. It was found that almost all students (98.4%) use sanitary latrine and only 1.6% didn’t. It was also found that about 98.9% students use soap after defecation and 1.1% use only water. Conclusions: The result shows that majority of the students heard the name of sanitary latrine and almost all students use sanitary latrine. So the knowledge and practices regarding use of sanitary latrine of primary school children is satisfactory.